Penggunaan Qris Dan Perubahan Pola Transaksi Keuangan Di Era Digital: Tinjauan Ekonomi Syariah - Ahmad Rezky Adenan; Tiara Muslimah; Erwan Setyanoor (PT. Saha Kreasi Indonesia, 2026)
The digital economic transformation has significantly altered financial transaction patterns, particularly through the transition from cash-based payments to digital systems. In Indonesia, the Quick Response Code Indonesian Standard (QRIS), introduced by Bank Indonesia, serves as a national standard for QR code–based digital payments. This study examines the role of QRIS in shaping financial transaction behavior in the digital era and evaluates its compatibility with Islamic economic principles. Using a library research method, this study analyzes academic literature, regulatory documents, and prior studies related to digital payments and Islamic finance. The findings indicate that QRIS enhances transaction efficiency, supports financial inclusion, and improves financial transparency, especially for micro, small, and medium enterprises (MSMEs). From an Islamic economic perspective, QRIS functions as a payment instrument and does not affect contract validity as long as transactions are conducted voluntarily, transparently, and free from riba, gharar, and maysir. Nevertheless, concerns remain regarding the fairness of the Merchant Discount Rate (MDR) if mutual consent is unclear. Overall, QRIS contributes to an inclusive and efficient digital financial ecosystem within Islamic economic principles.